Terrorism: Its Impact and Countermeasures - Siti Ma'sumah; Kholid Mawardi (PT. Multidisciplinary Press Indonesia, 2024)
Terrorism emerges due to the escalating presence of intense radical ideologies. While terrorism was once confined to specific physical locations and territories, the evolution of internet technology has expanded its reach significantly. This research employs a library-based methodology to examine and address a particular research issue. The findings of this study indicate that terrorist bombings have a substantial impact on air quality, leading to the degradation of human health and resulting in the death of numerous animals and livestock. Furthermore, these actions can also have a detrimental effect on the economy, as investors become apprehensive about investing and consumer purchasing power diminishes. The economy can experience a downturn due to a decrease in both foreign and domestic tourism, as interest in traveling wanes. Terror attacks that involve disrupting vital resources such as water and electricity supplies, as well as contaminating water sources with hazardous substances, pose a significant threat to human health and well-being. Every nation should undertake efforts to counter terrorism. In addition to establishing domestic laws, it is imperative for all countries worldwide to formulate their own constitutions to collectively denounce terrorism. A global commitment against terrorism must be fostered, with all nations working together to oppose this threat.